Understanding the mechanism of byproduct formation with in operando synchrotron techniques and its effects on the electrochemical performance of VO2(B) nanoflakes in aqueous rechargeable zinc batteries. Issue 19 (5th May 2020) - Pang, Qiang; Zhao, Hainan; Lian, Ruqian; Fu, Qiang; Wei, Yingjin; Sarapulova, Angelina; Sun, Junqi; Wang, Chunzhong; Chen, Gang; Ehrenberg, Helmut
Abstract : The byproduct protects the vanadium-based positive electrode of ARZBs and facilitates Zn 2+ insertion into the electrode. Abstract : Monoclinic VO2 (B) nanoflakes prepared by a hydrothermal method displayed superior electrochemical performance in 1 M ZnSO4 electrolyte. The reaction mechanisms of VO2 (B) and the essential causes of byproduct formation in aqueous rechargeable zinc batteries (ARZBs) were comprehensively studied by electrochemical measurements combined with in operando synchrotron techniques and first-principles calculations. During the electrochemical processes, the electrode underwent a reversible solid-solution reaction between VO2 (B) and Zn0.44 VO2 with the simultaneous formation/decomposition of the (Zn(OH)2 )3 (ZnSO4 )·5H2 O byproduct. Importantly, the formation of the byproduct was attributed to [Zn(H2 O)6 ] 2+ dehydration, where the byproduct could protect the electrode material from the corrosion of H3 O + and facilitate the dehydration process of Zn 2+ on the electrode–electrolyte interface. The byproducts could facilitate the migration of Zn 2+ on the electrode surface due to their three-dimensional pathways. In addition, the electrochemical performance of VO2 (B) and the byproduct in ZnSO4 electrolyte were compared with those in Zn(CF3 SO3 )2 and Zn(NO3 )2 . An appropriate electrolyte (1 M Zn(CF3 SO3 )2 ) to form a byproduct with largely expanded ionic pathways was proven to further improve the electrochemical performance of VO2 (B). This work not only provides a deep understanding of the Zn 2+ storage mechanism in VO2 (B) but also establishes a clear relationship between the byproducts and electrochemical performance of vanadium-based electrode materials in ARZBs.